Islam and Its Impact on Women's Status and Role in Egypt - Wahyuddin Halim (Universitas Islam Negeri Alauddin Makassar, 2015)
Gender relations in Islam has been the subject of serious debates among scholars in Egypt for many decades. One of the central questions was whether the status and role of women in Egypt were and are primarily influenced by Islam, or they should also be attributed to other social, economic, cultural and political factors. This study will look at the status and role of women in modern Egypt. It is commonly known that traditions based largely on religion (including Islam) and superstition are strong elements in the Egyptian culture. However, this study will show that the inequity in gender relations in modern Egypt should be more attributed to socioeconomic factors than to those religious or theological beliefs. On the other hand, one cannot overlook the formative influence of Islam on the roles of women and men in the country both in the past and in the present. The study suggests that attempts to reinterpret, reassess and re-actualize Islamic doctrines and practices pertaining to the equal status and roles of women in the context of Egyptian culture should also be considered in order to alter the women and men’s perception on gender relations.